2012
DOI: 10.1093/cvr/cvs129
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of glucose oxidation protects against acute myocardial infarction and reperfusion injury

Abstract: These findings demonstrate that stimulating glucose oxidation via targeting either PDH or MCD decreases the infarct size, validating the concept that optimizing myocardial metabolism is a novel therapy for ischaemic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
138
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 48 publications
10
138
0
2
Order By: Relevance
“…4 Besides the myocardial accumulation of toxic lipid intermediates, 16 fatty acids inhibit pyruvate dehydrogenase (PDH), the enzyme that links glycolysis to subsequent glucose oxidation by converting pyruvate to acetyl coenzyme A (CoA) for entry into the tricarboxylic acid cycle (Figure 2). 15,20 Conversely, increased glucose use inhibits fatty acid oxidation at the level of the enzyme carnitine palmitoyl transferase 1 (CPT-1), whereas increased malonyl-CoA levels produced by increased glucose flux potently inhibit this enzyme, thus providing a mechanism whereby high rates of aerobic glycolysis inhibit the oxidation of FFAs (Figure 3). 15,20,21 Compared with glucose, the β-oxidation of 1 mol palmitate yields significantly more ATP (129 versus 38 ATP per 1 mol substrate) but consumes more oxygen.…”
Section: Metabolism Of the Normal And Ischemic Heartmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Besides the myocardial accumulation of toxic lipid intermediates, 16 fatty acids inhibit pyruvate dehydrogenase (PDH), the enzyme that links glycolysis to subsequent glucose oxidation by converting pyruvate to acetyl coenzyme A (CoA) for entry into the tricarboxylic acid cycle (Figure 2). 15,20 Conversely, increased glucose use inhibits fatty acid oxidation at the level of the enzyme carnitine palmitoyl transferase 1 (CPT-1), whereas increased malonyl-CoA levels produced by increased glucose flux potently inhibit this enzyme, thus providing a mechanism whereby high rates of aerobic glycolysis inhibit the oxidation of FFAs (Figure 3). 15,20,21 Compared with glucose, the β-oxidation of 1 mol palmitate yields significantly more ATP (129 versus 38 ATP per 1 mol substrate) but consumes more oxygen.…”
Section: Metabolism Of the Normal And Ischemic Heartmentioning
confidence: 99%
“…15,20 Conversely, increased glucose use inhibits fatty acid oxidation at the level of the enzyme carnitine palmitoyl transferase 1 (CPT-1), whereas increased malonyl-CoA levels produced by increased glucose flux potently inhibit this enzyme, thus providing a mechanism whereby high rates of aerobic glycolysis inhibit the oxidation of FFAs (Figure 3). 15,20,21 Compared with glucose, the β-oxidation of 1 mol palmitate yields significantly more ATP (129 versus 38 ATP per 1 mol substrate) but consumes more oxygen. 22 FFAs are therefore the preferred substrate for the heart under normal conditions, and their uptake and use are determined primarily by their circulating concentrations.…”
Section: Metabolism Of the Normal And Ischemic Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…‡P Ͻ 0.05 for high-ketone compared with low-ketone with the same insulin level, perfusion condition, and diet. infarction and reperfusion injury (42), and an increased FFA oxidation has been associated with reduced myocardial tolerance to ischemia-reperfusion (13); therefore, any increase in FFA and decrease in CHO or ketone oxidation induced by HFLCD might lead to worsened cardiac function during I/R. This has led to the concept that repressing myocardial FFA oxidation may be a therapeutic target to improve cardiac efficiency in the ischemic heart (40).…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial glucose uptake and metabolism are essential for maintaining myocardial energetics especially under circumstances of stress, such as myocardial ischemia or hypertrophy (Patterson et al 2009). Indeed, stimulating glucose oxidation protects against acute myocardial infarction and reperfusion injury and is a potential therapeutic target (Ussher et al 2012). This may be especially important in patients with insulin resistance or type 2 diabetes, as multiple studies have shown defective myocardial glucose uptake and insulin resistance in these patients using fluorine 18-labeled fluorodeoxyglucose approaches (Iozzo et al 2002;Yokoyama et al 2000).…”
Section: Introductionmentioning
confidence: 99%